Research on wettability of spraying droplet with unmanned aerial vehicle - ZHENG Qishuai; CEN Haiyan; FANG Hui; WU Jianjian; XIAO Shupei; HE Yong (浙江大学学报. 农业与生命科学版)
In order to study the wettability of droplets on the leaves during aerial spraying and its influencing factors, orthogonal test and single factor test were applied to analyze the change of contact angle, which was affected by the location of leaf, foliar fertilizer type and concentration, adjuvant concentration, droplet size and instantaneous velocity. The results showed that the wettability of foliar fertilizer was effectively improved by adding adjuvants and ensuring the instantaneous velocity of the droplet at least 1.55 m/s. Liquid type and concentration, and droplet size had a certain influence on the wettability of foliar fertilizer, while the location of the leaf had no significant influence on the wettability of foliar fertilizer. The contact angle can reach 8.5° by applying the optimal combination, that is, spraying the reverse side of leaves, high concentration of Jiaduobao foliar fertilizer, 1% adjuvant and small droplets. This study can provide references for improving the effect of agricultural aerial spraying.